Historical and cultural significance and legal aspects of protection of ancient roads - Timofeev, Andrey N. (Journal of the Belarusian State University. Ecology, 2022)
In Russia, little attention is paid to such unique historical and cultural sites as ancient roads. Many roads that existed in the past have not been studied by scientists; information about them is contained in ancient manuscripts, legends and traditions. There is no cadastre of ancient roads in Russia, the legal and regulatory system for the protection of ancient roads and the methodology for separating them into the category of historical and cultural monuments and protected areas have not been properly developed. Most of the oldest roads in Russia still do not have the status of protected areas or historical and cultural monuments, which are an irreplaceable heritage of mankind. The article draws attention not only to the need to give the status of monuments and protected areas to the ancient roads of Russia, but also proposes criteria for a qualitative assessment of the historical and cultural lands on which the ancient roads are located. Five main criteria are described: 1) chronological, including three types of historical and cultural road objects - underground, ground and landscape; 2) saturation of the territory with road monuments of historical and cultural significance; 3) the significance of the historical and cultural road object for understanding domestic and world cultural and historical processes; 4) preservation of the historical and cultural road object; 5) the use of a historical and cultural road object in educational, cultural, educational and religious activities. The methodology uses a chronological approach to the qualitative assessment of historical and cultural land plots, which allows it to be carried out taking into account the peculiarities of the historical and ethno-cultural processes of each specific area. The basis of the methodological approach to the assessment of historical and cultural lands in this article is the principle of assessing lands according to the historical and cultural significance of objects located on these land plots, which make these lands historical and cultural. Based on this principle, the selection and justification of criteria were carried out, according to which a qualitative assessment of historical and cultural lands is made. Thus, the development of a method for assessing historical and cultural lands is a method of comparative assessment of historical and cultural objects.